Amorphous solid dispersions of ketoprofen and poly-vinyl polymers prepared via electrospraying and spray drying: A comparison of particle characteristics and performance. - Healy, Anne; Padamati, Ramesh (My University, 2019)
The purpose of this work was to compare the particle characteristics and dissolution performance of amorphous solid dispersions (ASDs) of ketoprofen and vinyl-pyrrolidone based polymers prepared using electrospraying and spray drying methods. Solution characteristics (surface tension, viscosity and conductivity) were determined for ethanolic solutions containing different vinyl-pyrrolidone based polymers (PVP and PVPVA) and different ketoprofen to polymer mass ratios. The only statistically significant difference in solution properties between PVP and PVPVA systems was electrical conductivity. The higher conductivity in PVP-containing solutions resulted in smaller, more spherical particles than the equivalent formulations prepared with PVPVA when processed via electrospraying. Electrospraying resulted in powders with higher specific surface area, smaller mean particle size, and narrower particle size distribution relative to the spray-dried material. Amorphisation of ketoprofen via both processes was confirmed using pXRD, DSC and FTIR. Although the specific surface area of the electrosprayed powder was higher than the equivalent spray-dried system, this did not translate into a faster dissolution rate at pH 1.2 but did lead to a faster surface moisture adsorption rate at various relative humidities. The flowability of the powder produced via the electrospraying process is poor compared to the equivalent powder produced via spray drying, which may cause challenges in downstream processing. While the ASD powder produced via electrospraying had a smaller particle size and narrower size distribution compared to equivalent spray-dried ASD, further refinement in terms of a final formulation is needed to translate this benefit into an improved dissolution rate in the case of ketoprofen.
PUBLISHED
Keywords: Amorphous solid dispersions; Electrospraying; Spray drying; Ketoprofen